PENGARUH KESEIMBANGAN KERJA PADA KEINGINAN BEKERJA PADA PT FREIGHT EXPRESS MEDAN - VISILLIA EDELWISA; KEVIN AZIS (JURNAL ILMIAH MAKSITEK, 2021)
PT Freight Express Medan is a company engaged in logistics delivery to the community, where the management of this company does not give full leeway for its employees to be able to balance between office and personal life, where there are still employees who are not appreciated when there is misfortune and there are also family events. and put more importance on work in the office, there are even employees who bring their work to the office. This situation makes employees feel uncomfortable and tend to be emotional facing the management, so many employees choose to resign and move to other companies, as a result, employee turnover increases and employee loyalty decreases. This study aims to determine whether employee work balance has a significant effect on the desire to work at PT Freight Express Medan. Data analysis in this study used validity and reliability tests, simple linear regression analysis and hypothesis testing, such as the coefficient of determination and t test, where the population in this study were employees of PT Freight Express Medan, amounting to 200 people, while the sampling method in this study used the accidental sampling method which was calculated using the slovin formula which in the end the number of samples that were successfully drawn were 40 employees.The results of this study indicate that the work balance variable has a significant influence on the employee's desire to continue working at PT Freight Express Medan.